Efektivitas Layanan Bimbingan Kelompok dengan Teknik Diskusi dalam Meningkatkan Keterbukaan Diri Siswa - Arlita, Monica; Hartini; Azwar, Beni; Apriani, Eka (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to demonstrate the effect of group guidance services with discussion techniques in increasing self-disclosure among class VIII B students at MTS Baitul Makmur. The study was conducted using an experimental method two group pretest-posttest control design. The population in the study were students of class VIII B MTS Baitul Makmur. The research sample consisted of 30 students, including 15 students from the experimental group and 15 students from the control group, taken using the technique purposive sampling. The results of the study showed that the level of self-disclosure in students before being given group guidance services with discussion techniques was in the low category and the level of self-disclosure of students who were not given treatment was also in the low category. Then, the level of self-disclosure of students after being given group guidance services with discussion techniques was in the medium category, while the level of self-disclosure of students without being given treatment was classified as low. The results of the t-test showed a value of -7.751 which means there is a difference in self-disclosure between students who received group guidance services with discussion techniques and students who did not receive treatment. Thus, the results of the study indicate that there is an influence of group guidance services with discussion techniques to increase the self-disclosure of class VIII B students at MTS Baitul Makmur.